Supply chain management strategy practices in Taiwan - Wu, Kuo Jui (Animo Repository, 2011)
This study investigates and demonstrates an analytical framework to assess a supply chain management strategy (SCMS). Selection of optimum supplier in a SCMS is estimated according to three primary levels, namely, criteria, attributes, and alternatives. The proposed hierarchical framework in deciding the appropriate suppliers can be applied with the assistance of the expert SCMS group. The evaluation framework is based on (i) multi-criteria decision making (MCDM) analysis which can determine the suitable alternative from the limited series of alternatives with regard to various conflicting criteria, and (ii) analytic network process (ANP) method which can consider the effect of feedback and variance dependence. It aids the case firm in identifying the main criteria in SCMS to gain a comprehensive and actual application. © 2011 IEEE.